The Role of Virtual Reality in Enhancing the Effectiveness of Teaching English for Specific Purposes - VEGA, Nofvia De; RAHAYU, Rahayu; BASRI, Nurfajriah (Politeknik Negeri Ujung Pandang, 2024)
This study provides a novel examination of the integration of Virtual Reality (VR) technology into English for Specific Purposes (ESP) instruction, specifically within the context of Management studies at Universitas Borneo Tarakan. It addresses a significant gap in empirical research by focusing on VR's effectiveness in teaching ESP within a management context, an area that has yet to be thoroughly explored. Using pre-and post-test scores from 286 students and detailed evaluation metrics, this research provides robust evidence of VR's transformative potential in enhancing ESP instruction. The findings indicate a clear improvement in language proficiency following VR-enhanced teaching, with significant increases in top-scoring students and decreases among those struggling with lower scores. Additionally, high levels of student engagement were observed during VR-enhanced lessons. Students reported positive usability experiences with the technology and expressed satisfaction with their learning outcomes. They also perceived significant benefits from using VR technology in their ESP instruction, including improved comprehension, increased motivation and engagement, and enhanced memory retention. However, alongside these positive outcomes are challenges that must be addressed for effective implementation. These include technical issues experienced by some participants suggesting the need for improvements or troubleshooting to enhance user experience; adaptation difficulties faced by learners when transitioning to new teaching methods introduced via virtual reality indicating the importance of providing additional support or guidance; and accessibility challenges emphasizing the need to ensure equal access for all learners when implementing such innovative technologies. In light of these findings, it is recommended that institutions like Universitas Borneo Tarakan looking to integrate VR into their ESP instruction consider establishing robust technical support structures to address potential issues. They should also provide additional guidance during transitions to new teaching methods introduced via virtual reality and prioritize ensuring accessibility for all learners. This study contributes valuable insights into effective strategies for modernizing ESP instruction using innovative technologies like Virtual Reality while highlighting areas where further exploration is needed.